The linear polymerisation shrinkage effect of chemical activated composite resin using different bonding agents on the dimensions of the tooth cavity - Mariam, Marry Siti; Cahyanto, Arief (Padjadjaran Journal of Dentistry, 2020)
Introduction: This study was aimed to determine the effect of the linear polymerisation shrinkage of composite resin using different bonding agents on the dimension of the tooth cavity. Methods: Fifty-four extracted human premolar teeth, both maxillary and mandibular were used and divided into three groups (A, B, and C) into eighteen specimens. The conventional cavity was prepared, and all cavities were bevelled. In Group A, only the bevel was etched, and the enamel bond was applied to it. Group B was treated with the same procedure as group A, but the dentin bond was used instead of enamel bond. Group C, the whole cavity was etched, dentin bond was applied on the bevel and the cavity walls. The reference points were placed in the vestibular and lingual palatal region as occlusal as possible on the enamel. The Silar® composite resin (microfilled, chemically activated), etching agent (gel etch), enamel and dentin bond system were employed for the preparation and filing of the cavities. The cavity was filled with composite, and the specimens were immersed in 0.02% chlorhexidine gluconate solution at the room temperature. The distance between both reference points was measured before and after filling procedures. Results: Group A showed the least shrinkage with a mean of 0.14%, group B showed a larger shrinkage with the average of 0.24% and the largest shrinkage was found in group C with the average of 0.26%. The difference between groups B and C was not statistically significant given at the point of 0.05 significance level, and the difference between groups A, B, and C was significant at the 0.01 significance level. From the mathematical modelling using the stress-strain equation, the results showed that the tensile stress in restrained of Silar® composite was higher than the enamel (19.80 MPa > 10.34 MPa) thus lead to cracks in the enamel. Conclusion: The acid etching on dentin is not improving the retention and marginal adaption of restorative resin. The use of enamel bond system gives a better effect on the adhesion strength compared to the dentin bond system.